KARAKTERISASI MUTAN KENTANG HITAM (Plectranthus rotundifolius (poir.) spreng.) HASIL IRADIASI SINAR GAMMA YANG TOLERAN SALINITAS DAN KEKERINGAN DENGAN MENGGUNAKAN MARKA RAPD DAN ISSR - Diyah Martanti; Yuyu S. Poerba; Kusumadewi Sri Yulita; Herlina Herlina (Widyariset, 2014)
Hausa potato (Plectranthus rotundifolius (Poir.) Spreng.) is one of the alternative food for people living in some part of Indonesia. However, its low level of genetic variations has become an obstacle in developing new va- riety. Plant breeding through mutation, e.g. irradiation of γ rays, can be assumed to improve genetic diversity. The aim of this study was to characterize tuber hausa potato mutant irradiated γ rays in salinity and drought tolerant using ISSR and RAPD markers. Five primers of ISSR and five primers of RAPD were used to amplify DNA of hausa potato mutants. Ten primers generated 95% polymorphic and 27 speciific band of irradiated salt-tolerant mutans. Meanwhile, they generated 49% polymorphic and three specific band of irradiated drought-tolerant mutans. The result of the Principal Component Analysis showed that mutants were divided into three groups based on specific bands that play role in the group formation. The result showed that the ISSR and RAPD markers can be reliable to characterize mutants on hausa potatoes.